Immunoassay quantification using surface-enhanced fluorescence (SEF) tags - Camacho, S. A. [UNESP]; Sobral-Filho, R. G.; Aoki, P. H.B. [UNESP]; Constantino, C. J.L. [UNESP]; Brolo, A. G. (Royal Society of Chemistry (RSC), 2017)
Fluorescence-based immonoassays are widely used in several areas, ranging from basic biomedical research to disease diagnostics. A variety of new probes have been developed recently to address some limitations in typical assays performed with organic dyes. Ideally, new fluorescence tags that allow quantification with a low limit of detection are highly desired. In this work, the surface-enhanced fluorescence (SEF) phenomenon was explored in the development of tags for Immunoglobulin-M (IgM) detection. Shell-isolated gold nanoparticles (Au-SHINs) with 100 nm core size and a 10 nm silica shell were synthesized. These particles contain an outermost thin fluorescent layer of nile blue (NB) that was further coated by another 5 nm of silica (SEF tags). The outer silica shell was then functionalized with antibodies to allow the detection of IgM as in typical immunological sandwich assays. IgM concentrations down to the 10 ng mL-1 mark were successfully detected. A linear dependence between the average fluorescence intensity and the IgM concentration was found.